2010
DOI: 10.1017/is010001014jkt105
|View full text |Cite
|
Sign up to set email alerts
|

Bimonads and Hopf monads on categories

Abstract: Abstract. The purpose of this paper is to develop a theory of bimonads and Hopf monads on arbitrary categories thus providing the possibility to transfer the essentials of the theory of Hopf algebras in vector spaces to more general settings. There are several extensions of this theory to monoidal categories which in a certain sense follow the classical trace. Here we do not pose any conditions on our base category but we do refer to the monoidal structure of the category of endofunctors on any category A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 26 publications
(25 reference statements)
0
81
0
Order By: Relevance
“…An endofunctor allowing for a monad and a comonad structure may be a Frobenius monad if the compatibility conditions in Proposition 1.17 are satisfied, or one may impose other compatibility requirements leading to the definition of (see [11,Definition 4.1]) 2.4. Bimonads.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…An endofunctor allowing for a monad and a comonad structure may be a Frobenius monad if the compatibility conditions in Proposition 1.17 are satisfied, or one may impose other compatibility requirements leading to the definition of (see [11,Definition 4.1]) 2.4. Bimonads.…”
Section: 2mentioning
confidence: 99%
“…The and it can be shown that this λ is a mixed entwining (see [11,Proposition 6.3]). Of course, not every mixed entwining has to be of this form.…”
Section: 3mentioning
confidence: 99%
“…The conditions required in 5.4 make the functor B ⊗ R − a bimonad on R M in the sense of [20,Definition 4.1]. In general they do not imply the same property for the functor − ⊗ R B on M R .…”
Section: Mixed Liftingsmentioning
confidence: 99%
“…Among bialgebras, Hopf algebras are characterised by the fact that the functor B ⊗ R − : R M → B B M is an equivalence (e.g. [20,Theorem 6.12]). …”
Section: Mixed Liftingsmentioning
confidence: 99%
“…Now, considering the monad and comonad [B, −] = Hom(B, −), we can also define bimodules leading to the category M These relationships are explained in more detail in [1]. It is shown in [5] and [7] how they can be transferred to bimonads on arbitrary categories.…”
Section: 11mentioning
confidence: 99%